2016
DOI: 10.3758/s13423-016-1043-4
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial working memory influences the interaction between space and time

Abstract: How do representations of space inform our perception of time? In language, spatial vocabulary is frequently used to describe temporal concepts, and spatial information biases temporal perception even in non-verbal tasks. In contrast, temporal information typically exerts little, if any, influence on the perception of spatial extent. Here, we used spatial and temporal reproduction tasks, both with and without verbal and spatial dual tasks, to investigate the mechanism underlying the asymmetric relation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…When spatial task is highly demanding, participants are more influenced by irrelevant temporal information. The overall findings corroborate recent evidence for a role of visuospatial working memory in space-time interference (Starr & Brannon, 2016) and support the interpretation of space-time interference in terms of gradient of automaticity.…”
Section: Introductionsupporting
confidence: 88%
“…When spatial task is highly demanding, participants are more influenced by irrelevant temporal information. The overall findings corroborate recent evidence for a role of visuospatial working memory in space-time interference (Starr & Brannon, 2016) and support the interpretation of space-time interference in terms of gradient of automaticity.…”
Section: Introductionsupporting
confidence: 88%
“…In particular, future studies need to (1) explore their contribution to bias effects in dual-magnitude-judgment tasks (eg., Casasanto & Boroditsky, 2008; Merritt, Casasanto, & Brannon, 2010; Starr & Brannon, 2016), (2) their contribution to binding together two or more magnitude measurements in memory (eg., Srinivasan & Carey, 2010), and (3) whether ratios are calculated in a centralized module.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Starr and Brannon (2016) showed that, while filled length unilaterally biases durations under no working memory load or under verbal working memory load (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while mutual interference has been observed between size and numerical magnitude (Henik & Tzelgov, 1982;Kaufmann et al, 2005;Szucs & Soltesz, 2007) and between length and numerosity (Dormal & Pesenti, 2013), previous research has shown that duration is influenced by, but does not influence, concurrent non-temporal magnitudes such as numerosity (Dormal & Pesenti, 2013;Dormal, Seron, & Pesenti, 2006), number (Droit-Volet, Clément, & Fayol, 2003 and length (Casansato & Boroditsky, 2008;Casasanto, Fotakopoulou, & Boroditsky, 2010;Magnani et al, 2014;Starr & Brannon, 2016). While in some cases duration is observed to also influence the estimation of a concurrent dimension such as length, the effect of duration on length is shown to be much smaller than the effect of length on time (Merritt et al, 2010; but see Cai & Connell, 2015, discussed below).…”
mentioning
confidence: 99%